(untitled) (JED (Jurnal Etika Demokrasi), 2022)
The degradation of multicultural character in students is supported by concerns about this, the teacher as one of the things that must shape the character of students does not have basic values that must be used in the context of multicultural character in students. The purpose of this study is to re-analyze the values of Pancasila that can be used by teachers as a basis for forming multicultural characters in students. In this study used library research methods (Library Research). After analyzing several variables that become benchmarks in forming multicultural characters, among others: As a basis for social competence, social learning for the development of integrated intelligence, strengthening multicultural characters carried out in an institutionalized manner. This page is in English Translate to Indonesian Afrikaans Albanian Amharic Arabic Armenian Azerbaijani Bengali Bulgarian Catalan Croatian Czech Danish Dutch English Estonian Finnish French German Greek Gujarati Haitian Creole Hebrew Hindi Hungarian Icelandic Indonesian Italian Japanese Kannada Kazakh Khmer Korean Kurdish (Kurmanji) Lao Latvian Lithuanian Malagasy Malay Malayalam Maltese Maori Marathi Myanmar (Burmese) Nepali Norwegian Pashto Persian Polish Portuguese Punjabi Romanian Russian Samoan Simplified Chinese Slovak Slovenian Spanish Swedish Tamil Telugu Thai Traditional Chinese Turkish Ukrainian Urdu Vietnamese Welsh Always translate English to IndonesianPRO Never translate English Never translate journal.unismuh.ac.idTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//